Refining national culture and entrepreneurship: The role of subcultural variation - Dave Valliere (Journal of Global Entrepreneurship Research, 2019)
This study investigates attitudes towards entrepreneurship within a national culture. The effects of culture represent the most significant and unexplored factor in current theories of entrepreneurial intentions. The study uses Q methodology to conduct a hybrid qualitative and quantitative exploration of the attitudes about entrepreneurship that are present within the cultural discourse. Within one region of Canada, three distinct viewpoints are discovered which share many attitudes about entrepreneurship, but which also feature clear differences in their potential to positively or negative influence beliefs and attitudes of individuals. This study contributes to a theory by demonstrating that culture is multidimensional and heterogeneous in the way that broad constructs of "national culture" are translated into influences on individual traits and characteristics.
Keywords: 650; Entrepreneurial intent; Culture; Subjective norms; Theory of planned behaviour; Q methodology